Revenue Generation and Organisational Change in Higher Education Insights from Canada - Eastman, Julia Antonia (OECD Publishing, 2006)
This paper reports on a study of four major Canadian universities' strategies for generating revenue in the face of prolonged cutbacks. The universities are placed on a continuum of higher education funding, institutional types and organisational attributes. The study produced new hypotheses about how universities' organisational attributes change as a result of the need to generate revenue